2013
DOI: 10.1002/smr.1621
|View full text |Cite
|
Sign up to set email alerts
|

Towards a hybrid testing process unifying exploratory testing and scripted testing

Abstract: SUMMARY Given the current state of the art in research, practitioners are faced with the challenge of choosing scripted testing (ST) or exploratory testing (ET). This study aims at systematically incorporating strengths of ET and ST in a hybrid testing process to overcome the weaknesses of each. We utilized systematic review and practitioner interviews to identify strengths and weaknesses of ET and ST. Strengths of ET were mapped to weaknesses of ST and vice versa. Noblit and Hare's lines‐of‐argument method wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 32 publications
(55 reference statements)
1
9
0
Order By: Relevance
“…The three top-ranked advantages of ET mentioned by respondents are "Supports creativity", "Efficient", and "Effective". This largely corresponds to what other researchers have found, e.g., Shah et al [18] and Itkonen et al [7][9]. The three top-ranked disadvantages of ET mentioned by respondents are "high requirement for tester", "inflexible", "hard to record", "not good for complicated project".…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…The three top-ranked advantages of ET mentioned by respondents are "Supports creativity", "Efficient", and "Effective". This largely corresponds to what other researchers have found, e.g., Shah et al [18] and Itkonen et al [7][9]. The three top-ranked disadvantages of ET mentioned by respondents are "high requirement for tester", "inflexible", "hard to record", "not good for complicated project".…”
Section: Discussionsupporting
confidence: 87%
“…In a recent article, Shah et al conducted a comprehensive literature survey and interviews to investigate into strengths and weaknesses of ET and scripted testing [18]. Regarding strengths, the authors found ET to be cost-effective due to little and focused documentation, good resource utilization, rapid feedback, and quick familiarization with the product.…”
Section: Related Workmentioning
confidence: 99%
“…ST is a plan-driven testing process where test cases are designed prior to test execution in order to structure and to guide the testing tasks. This approach provides several benefits such as test awareness, test coverage, repeatability, and tracking [1], [17].…”
Section: Introductionmentioning
confidence: 99%
“…A few studies such as [9], [16], [17] mentioned that ET makes better use of testers creativity and skills to discover the bugs that ST may not uncover because of its mechanical nature. On the other hand, some shortcomings of the ET approach have been also reported such as; the difficulty in assessing whether all features are tested, unavailability of oracles, and invisibility of the quality of testing [16], [17], [18].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation